EFFECTS OF EMOTIONAL INTELLIGENCE ENHANCING PROGRAM ON SOCIAL INTELLIGENCE AMONG NURSING STUDENTS - Bundasak, Thanapol; Chaowieng, Kanok-on; Tantisuwichwong, Saovaluk; Jangasem, Narumol; Yotkhamlue, Kwanchanok (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
Social Intelligence is a significant factor for nursing students to have good social skills, adaptive ability, and effective working with others. This quasi-experimental study aimed to test the effects of Emotional Intelligence Enhancing (EIE) program on social intelligence among nursing students. The study sample was 52 first-year nursing students in Boromarajonani College of Nursing, Phraphutthabat (BCNPB) who met the inclusion criteria. These students were randomly assigned to an experimental group (n=26) and a control group (n=26). The experimental group received the EIE program twice a week, a total of eight times, and 60-90 minutes per time. The control group received usual care from BCNPB. Data were collected by using the social intelligence questionnaire that was tested for the reliability of .86. The data were analyzed by descriptive statistic, independent t-test, two ways repeated measure ANOVA, and multiple comparisons by Bonferroni. The results revealed as follows: At the post-test and 1-month follow-up period, the experimental group had statistically significantly higher mean scores of social intelligence than the control group (p=.000). After receiving the EIE program, at post-test and 1-month follow-up period, the experimental group had statistically significantly higher mean scores of social intelligencethan the pre-test period (p=.000).